Effectiveness of the Task-Based Language Teaching Method in Improving Foreign Language Writing Skills - febrianti, mariska; Praja Dinata, Ridho; Miranty, Delsa; Rasita Gloria, Irma; Chairil Imran, Muhammad (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Foreign language teaching has experienced a shift towards a more task-oriented approach to improving language skills. However, not much research has explored the effectiveness of the Task-Based Language Teaching method in the world of physical education, foreign language education, and elementary school teacher education. For this reason, the Task-Based Language Teaching method is used as a solution to improve the skills of students in physical education, foreign language education and elementary school teacher education. Purpose. This research aims to evaluate the effectiveness of the Task-Based Language Teaching method in improving students' language skills in three different fields of study. Method. This research uses a quantitative approach with a pre-post test experimental design. Results. The results of this study indicate that there was an increase in language skills in the experimental group who received training using the Task-Based Language Teaching method compared to the control group. Physical education students showed improvements in speaking and writing skills, while foreign language education and elementary school teacher education students showed improvements in listening and speaking abilities. Conclusion. The conclusion of this research shows that the Task-Based Language Teaching method is effective in improving students' language skills in various fields of study, including physical education, foreign language education, and elementary school teacher education. Implementation of the Task-Based Language Teaching method can be an effective alternative in enriching language teaching, improving communication skills, and providing a more contextual and relevant learning experience for students.